MOTIVASI MAHASISWA DALAM MENGIKUTI PERKULIAHAN BOLA VOLI - M. Taheri Akhbar (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract - Motivation of students in following the bolavoli training of sports faculty of FKIP Universitas PGRI Palembang. The problem in this research is still some of the students are less eager, willingness to follow bolavoli lecture. The purpose of this study to determine the motivation of students in following bolavoli lectures. The research method used quantitative descriptive method. The population in this research is 26 students. Data collection techniques in this study using a questionnaire to measure student motivation. The population of 26 sample students was taken by the whole population. Data analysis technique used is frequency distribution technique with percentage calculation P = F / Nx100%. The results of this study indicate that the answers of 26 students who became respondents who followed the bolavoli lecture, from the respondents obtained the results of data analysis and description of student motivation results in following the bolavoli lecture is the average (mean) for attention indicator 4.32 with the percentage 86.48% is well classified, (mean) for pleasure indicator 4.38 with 87.54% percentage rate is very well classified, and (mean) for willingness indicator 4.34 with percentage level 86.81% is very well classified. From the total is obtained (mean) student motivation in following lecture bolavoli = 4,35 with percentage level 86,95% very well classified, meaning 13,05% influenced by other factor. Based on the above data it can be concluded that the motivation of students in the bolavoli lecturing program of FKP Univ PGRI Palembang is considered very good. Keywords: Motivation, Bola voli Lecture Abstrak - Motivasi mahasiswa dalam mengikuti perkuliahan bolavoli prodi olahraga FKIP Universitas PGRI Palembang. Masalah dalam penelitian ini adalah masih adanya sebagian mahasiswa kurang bersemangat, kemauan dalam mengikuti perkuliahan bolavoli. Tujuan penelitian ini untuk mengetahui motivasi mahasiswa dalam mengikuti perkuliahan bolavoli. Metode penelitian yang digunakan metode deskriptif kuantitatif. Populasi dalam penelitian ini adalah 26 orang mahasiswa. Teknik pengumpulan data dalam penelitian ini menggunakan angket untuk mengukur motivasi mahasiswa. Populasi berjumlah 26 orang mahasiswa sampel diambil keseluruhan anggota populasi. Teknik analisis data yang digunakan adalah teknik distribusi frekuensi dengan perhitungan persentase P=F/Nx100%. Hasil penelitian ini menunjukkan bahwa jawaban dari 26 orang mahasiswa yang menjadi responden yang mengikuti perkuliahan bolavoli, dari responden tersebut didapatkan hasil analisis data dan deskripsi hasil motivasi mahasiswa dalam mengikuti perkuliahan bolavoli yaitu rata-rata (mean) untuk indikator perhatian 4,32 dengan tingkat presentase 86.48% diklasifikasikan baik sekali, (mean) untuk indikator kesenangan 4.38 dengan tingkat presentase 87.54% diklasifikasikan baik sekali, dan (mean) untuk indikator kemauan 4.34 dengan tingkat presentase 86.81% diklasifikasikan baik sekali. Dari keseluruhan didapat (mean) motivasi mahasiswa dalam mengikuti perkuliahan bolavoli = 4,35 dengan tingkat persentase 86,95% dikasifikasikan baik sekali, artinya 13,05% dipengaruhi oleh faktor lain . Berdasarkan data di atas dapat disimpulkan motivasi mahasiswa dalam mengikuti perkuliahan bolavoli prodi olahraga FKP Univ PGRI Palembang dikategorikan baik sekali. Kata Kunci : Motivasi, Perkuliahan Bola voli